Exploring the trajectories of highly skilled migration law and policy in Japan and the UK - Daisuke Wakisaka; Paul James Cardwell (Comparative Migration Studies, 2021)
Abstract Japan and the UK appear to have few commonalities in terms of their history of and approach to migration law and policy. However, strong similarities in their contemporary approaches can be detected. Migration sits at the very top of the national political agendas and both have undertaken successive, major policy reforms over the past decade. Both have governments publicly committed to policies to attract ‘highly skilled’ migrants, with a restrictive approach towards ‘unskilled’ migrants. This article draws out the similarities and differences of migration law and policy in Japan and the UK via their respective legislative structures and policy trajectories on highly skilled migration. The article argues that Japan and the UK promote a market-driven model which enables highly skilled migration to be ‘sold’ to publics believed to be hostile to increased migration. Yet, the rapid changes in policy and revising of applicable rules often prevents the successful recruitment of highly skilled migrants to both countries.